THE ROLE OF MANAGERIAL COMPETENCIES IN ENHANCING HUMAN POTENTIAL AND ORGANIZATIONAL INNOVATION IN UZBEKISTAN - Shoyunusova Arofat (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA’LIMNING INNOVATSION YO’NALISHLARI, 2025)
This article explores how the development of managerial competencies contributes to strengthening human potential, organizational innovation, and sustainable growth in Uzbekistan. In an era defined by digital transformation and global competition, effective management practices play a decisive role in unlocking employee creativity, improving institutional performance, and building adaptive organizations. The paper examines how Uzbekistan’s managerial reforms—particularly in education, business, and the public sector—help shape a new generation of leaders capable of fostering innovation and motivating human resources. The study also highlights the importance of leadership ethics, communication, and talent management as central pillars of contemporary management practice. It concludes that cultivating managerial competencies and organizational learning culture is fundamental for ensuring competitiveness and inclusive development in Uzbekistan.